Determinants of consumer intention towards halal cosmetic products: the cage of community in Gerik, Perak / Umi Azmira Rosly - Rosly, Umi Azmira (Faculty of Business and Management, 2018)
The objective of this paper is to identify the major determinants of consumer intention towards halal cosmetic products. For this research, the dependent variable is the determinants of consumer intention towards halal cosmetic products and the independent variables are religiosity, knowledge and attitudes. This research uses a quantitative research method where a total amount of 150 questionnaires were distributed to the consumer in the area of Gerik, Perak. A simple random sampling was used to obtain information. The data which is primary data was being collected through questionnaire either through face to face or mail. The data also were analysed using [BM Statistics package for Social Science (SPSS) version 22. The result was analysed by using the descriptive statistical test, reliability test, correlation analysis and regression analysis from a sample size of 150 respondents who is the resident at Gerik, Perak. Cronbach's Alpha reliability test is performed for each variable. The entire variable has a good and acceptable Cronbach's Alpha value. This study found that there were significant relationship between religiosity, knowledge and attitudes with consumer intention. From the previous study, it indicates that there is a positive relationship between attitude and intention to choose Halal cosmetic products. The findings of the result from regression analysis indicated that attitudes were the major determinants of consumer intention towards halal cosmetic products. The implication of this study is to ensure that consumers who used the cosmetic products must 100k for the existence of halal logo stamped on the products so that the products can be surely being used especially for the Muslim consumers. Other than that, it can also help the consumer to make the right decision when making purchasing decision.